Kaiju no. 8. 9 - Matsumoto, Naoya, 1982- (Shonen Jump manga., 2024)
"With the highest kaiju-emergence rates in the world, Japan is no stranger to attack by deadly monsters. Enter the Japan Defense Force, a military organization tasked with the neutralization of kaiju. Kafka Hibino, a kaiju-corpse cleanup man, has always dreamed of joining the force. But when he gets another shot at achieving his childhood dream, he undergoes an unexpected transformation. How can he fight kaiju now that he's become one himself?! With the looming threat of a cataclysm induced by No. 9, the next generation of the Defense Force takes steps to prepare. Reno undergoes training and becomes the first compatible user of No. 6 in history. Kafka sharpens his skills by learning squadron-style combat techniques under Hoshina's tutelage. Meanwhile, Kikoru gets clearance from Narumi to inherit a powerful memento that once belonged to her mother."--Back cover.